Hemoglobin Savannah (B6(24) β-glycine→valine): an unstable variant causing anemia with inclusion bodies - Huisman, T. H. J. (1971)
An abnormal hemoglobin, termed Hb Savannah, was found in red cell hemolysate of a young Caucasian girl with severe hemolytic anemia. The presence of this unstable variant became evident when inclusion bodies appeared rapidly upon exposure of red cells to redox dyes and a large percentage of hemoglobin in hemolysate precipitated on warming to 65°C. Treatment of the hemoglobin with p-hydroxymercuribenzoate (PMB) caused a rapid dissociation into monomers; starch-gel electrophoresis of PMB-treated hemoglobin showed the presence of abnormal β-chains. Data from structural studies of isolated β-chains indicated substitution of a valyl residue for the normally occurring glycyl residue at position 24, which corresponds to helical residue B6. A similar substitution but with an arginine replacing the glycyl residue has been observed in Hb Riverdale-Bronx. The glycine to valine substitution will change the relationship of the B and the E helices which results in extensive conformational changes in the β-chain. This change presumably causes an increased dissociation of the hemoglobin molecule into dimers and probably monomers, and a decreased stability of the αβ-dimers. The hemoglobin abnormality may be the result of a fresh mutation because the abnormality is not present in the parents nor in any of the seven siblings.